2013
DOI: 10.1177/003335491312800612
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity and Reliability of Three Indicators Self-Reported on the Pregnancy Risk Assessment Monitoring System Survey

Abstract: Objectives. We investigated the reliability and validity of three self-reported indicators from the Pregnancy Risk Assessment Monitoring System (PRAMS) survey.Methods. We used 2008 PRAMS (n515,646) data from 12 states that had implemented the 2003 revised U.S. Certificate of Live Birth. We estimated reliability by kappa coefficient and validity by sensitivity and specificity using the birth certificate data as the reference for the following: prenatal participation in the Special Supplemental Nutrition Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…PRAMS uses maternal self‐report and thus recall bias is possible, though unlikely , as well as social desirability bias toward increased breastfeeding. Additionally, PRAMS does not ask mothers to differentiate between direct breastfeeding versus pumping and bottle feeding, nor does it quantify the proportion breast milk versus formula, which may have implications on child health .…”
Section: Discussionmentioning
confidence: 99%
“…PRAMS uses maternal self‐report and thus recall bias is possible, though unlikely , as well as social desirability bias toward increased breastfeeding. Additionally, PRAMS does not ask mothers to differentiate between direct breastfeeding versus pumping and bottle feeding, nor does it quantify the proportion breast milk versus formula, which may have implications on child health .…”
Section: Discussionmentioning
confidence: 99%
“…A blood sample was drawn at baseline to confirm HIV status and measure CD4 cell count. A structured face-to-face questionnaire was completed at enrollment to collect information on sociodemographics; depression and health [17]; reproductive history; partnership dynamics (for example, HIV serostatus disclosure, partner HIV serostatus); perception, use, and knowledge of contraception; decision-making [18][19][20][21][22][23]; food insecurity [24,25]; alcohol use in the last year [26]; HIV stigma [27]; social support [28]; and pregnancy intentions or aspiration [29][30][31].…”
Section: Study Measuresmentioning
confidence: 99%
“…While studies have demonstrated that PRAMS self-report measures of breastfeeding initiation show a high degree of agreement with the birth certi cate (47), similar studies evaluating post-hospital breastfeeding outcomes are not available. We estimate that on average, breastfeeding duration may have been mildly overestimated due to social desirability bias, however, we do not believe this would be differential with respect to the exposure of interest, and therefore feel any bias in the effect estimates reported is likely in the direction of the null hypothesis.…”
Section: Discussionmentioning
confidence: 99%